D-lactate-triggered extracellular trap formation in cattle polymorphonuclear leucocytes is glucose metabolism dependent. (October 2022) - Quiroga, John; Alarcón, Pablo; Manosalva, Carolina; Teuber, Stefanie; Carretta, María Daniella; Burgos, Rafael Agustín
Abstract: D-lactic acidosis is a metabolic disease of cattle caused by the digestive overgrowth of bacteria that are highly producers of d -lactate, a metabolite that then reaches and accumulates in the bloodstream. d -lactate is a proinflammatory agent in cattle that induces the formation of extracellular traps (ETs) in polymorphonuclear leucocytes (PMN), although information on PMN metabolic requirements for this response mechanism is insufficient. In the present study, metabolic pathways involved in ET formation induced by d -lactate were studied. We show that d -lactate but not l -lactate induced ET formation in cattle PMN. We analyzed the metabolomic changes induced by d -lactate in bovine PMN using gas chromatography-mass spectrometry (GC-MS). Several metabolic pathways were altered, including glycolysis/gluconeogenesis, amino sugar and nucleotide sugar metabolism, galactose metabolism, starch and sucrose metabolism, fructose and mannose metabolism, and pentose phosphate pathway. d -lactate increased intracellular levels of glucose and glucose-6-phosphate, and increased uptake of the fluorescent glucose analog 2-NBDG, suggesting improved glycolytic activity. In addition, using an enzymatic assay and transmission electron microscopy (TEM), we observed that d -lactate was able to decrease intracellular glycogen levels and the presence of glycogen granules. Relatedly, d -lactate increased the expression of enzymes of glycolysis, gluconeogenesis and glycogen metabolism. In addition, 2DG (a hexokinase inhibitor), 3PO (a 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase 3 inhibitor), MB05032 (inhibitor of fructose-1, 6-bisphosphatase) and CP-91149 (inhibitor of glycogen phosphorylase) reduced d -lactate-triggered ETosis. Taken together, these results suggest that d -lactate induces a metabolic rewiring that increases glycolysis, gluconeogenesis and glycogenolysis, all of which are required for d -lactate-induced ET release in cattle PMN. Highlights: d -lactate increases the intracellular levels of glucose, glucose-6-phosphate and glucose-1-phosphate in bovine neutrophils. D-lactate increases glucose metabolism through glycolysis, gluconeogenesis and glycogen metabolism. Glycolysis, gluconeogenesis and glycogenolysis are all metabolically necessary for d -lactate-induced NET release in cattle.